Understanding inequalities : stratification and difference - Platt, Lucinda (Polity Press, 2011)
Explores social inequalities and the part they play in people's day-to-day lives, a core concern of sociology* Importantly moves beyond the traditionally well-covered areas of gender, race and class, to engage with a wider range of inequalities